Variant in CAPN10 gene and environmental factors show evidence of association with excess weight among young people in a Colombian population (2014)
ABSTRACT: Obesity results from interaction between genetic and environmental risk factors. Objective: To evaluate the effect of three gene variants and environmental factors on obesity and overweight in young people aged 10 to 18 years in a Colombian population. Materials and methods: A total of 424 subjects were selected and separated into three groups for a cross-sectional study; 100 obese and 112 overweight subjects were matched with 212 normal-weight controls. Associations were evaluated between excess weight and three genetic polymorphisms (UCP3- rs1800849, FTO-rs17817449, and CAPN10-rs3842570), as well as the family history, the time spent watching television and playing video games, and the diet. Results: A family history of obesity, the time spent watching television and playing video games, the lack of breastfeeding, a low consumption of cereals, legumes, fruits, vegetables, and a high consumption of fast foods were characteristics typically found in obese individuals compared to controls. A significant association between genotype I/I (SNP19 of CAPN10) and excess weight was found even with an active lifestyle. In addition, significant associations between the C/C genotype of the UCP3 gene and the G/G and T/T genotypes of the FTO gene and excess weight were found only in young sedentary individuals. Conclusions: In this population, inadequate diet and sedentary lifestyle increased the risk of excess weight. Genotype I/I of SNP19 in CAPN10 was significantly associated with excess weight. In contrast, FTO and UCP3 variants exhibited effects only in sedentary environments.